Guinea Bissau Citizen Engagement : Policy Note on Inclusive on Inclusive Service Delivery - World Bank (World Bank, Washington, DC, 2020)
Despite higher levels of poverty and extreme poverty in rural areas, access to basic services outside the capital is limited in Guinea-Bissau. The state’s weak presence beyond Bissau has meant that donors, working in partnership with local non-governmental organizations (NGOs), have become an alternative service provider, leaving the country heavily dependent on development partners. Only 1 percent of its investment program is financed by domestic finances and there is little coordination of donors, leading to gaps and duplication. Despite decentralization efforts, local governments lack the capacity to provide basic services. Therefore, in the short term, the focus should be on creating a development partnership framework (DPF) to establish a system for planning, monitoring, and evaluating development efforts. This framework should be set up in an incremental fashion, starting with (i) establishing a transitory DPF while the government puts in place the enabling actions needed; (ii) establishing an Aid Coordination Unit within the office of the Prime Minister to support the overall implementation of the DPF; (iii) creating an Aid Management Information System to act as a single repository for all aid information; and (iv) institutional development and capacity building to improve the efficiency and effectiveness of development programs and ensure a transparent and accountable planning and budget process.